Isoenzyme patterns of Trialeurodes vaporariorum and Bemisia tabaci (Homoptera, Aleyrodidae) and of Encarsia formosa and E. lycopersici (Hymenoptera, Aphelinidae) - Oliveira, Maria Regina Vilarinho de; Lima, Lúzia Helena Correia de (Pesquisa Agropecuaria Brasileira, 1997)
The economic importance of whiteflies as pests of cultures has increased significantly in different regions of the world. Electrophoretic analysis of isoenzyme de a and b esterase was used as molecular marker in order to determine the genetic variation between individuals of whiteflies species, Trialeurodes vaporariorum (Westwood) and Bemisia tabaci (Gennadius) (Homoptera, Aleyrodidae) and the parasitoids E. formosa Gahan and E. lycopersici De Santis (Hymenoptera, Aphelinidae), and to assist in the identification of species or biotypes in future investigations of these species collected in different geographical areas. Both populations sampled, the whiteflies and the parasitoids, revealed different isoenzyme patterns of a and b esterases, enabling the differentiation between species and the distinction of whiteflies males and females.